Manifestation of Side Effects of Chemotherapy in Pediatric Patients. 4-year Observation Results - Nanobashvili, Ketevan; Nikoleishvili, Elza (Caucasus Journal of Health Sciences and Public Health, 2020)
Chemotherapy occupies a special place in the various schemes of treatment of oncological diseases. Of the ten most common drug reactions (ADRs) are follows: complications, nausea +/- Vomiting, weakness, alopecia, drowsiness, myelosuppression, skin reactions, anorexia, mucositis and diarrhea. The scale of adverse reactions to chemotherapeutic drugs (ADRs) for oncology patients is colossal. Treatment of diseases caused by adverse drug reactions requires a lot of effort and additional finances. Our focus was on changes occurred during cancer treatment and after chemotherapy. Such pathological changes, which can aggravate oral health, are: vomiting, nausea, xerostomia, loss of appetite, diarrhea, complications, stomatitis, change in taste, metallic taste during infusion, mucosal ulcers (mucositis), unusual bleeding (from the nose and mouth), petechiae. In most patients may develop the deterioration of oral health. This factor can also have a significant effect on future permanent occlusion (if chemotherapy is given during a period of temporary occlusion), as well as conditions such as dysphagia, dysphonia, abnormalities in the development of oral structures.